2018
DOI: 10.1063/1.5023171
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fluorescence enhancement for slowly diffusing single molecules in plasmonic near fields

Abstract: Gold nanorods are extensively used for single-molecule fluorescence enhancement as they are easy to synthesize, bio-compatible, and provide high light confinement at their nanometer-sized tips. The current way to estimate fluorescence enhancement relies on binned time traces or on fluorescence correlation spectroscopy. We report on novel ways to extract the enhancement factor in a single-molecule enhancement experiment, avoiding the arbitrary selection of one or a few high-intensity burst(s). These new estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The intensities of the bursts in the time traces depend on the orientation and spatial position of the molecules with respect to the gold nanorods during their residence within the hot spot. As an approximation, we represented the maximum enhanced fluorescence as the largest intensity of the bursts in the time trace, subtracting the background . Those maximum bursts are around 55 counts/ms, whereas the background is 16 counts/ms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensities of the bursts in the time traces depend on the orientation and spatial position of the molecules with respect to the gold nanorods during their residence within the hot spot. As an approximation, we represented the maximum enhanced fluorescence as the largest intensity of the bursts in the time trace, subtracting the background . Those maximum bursts are around 55 counts/ms, whereas the background is 16 counts/ms.…”
Section: Resultsmentioning
confidence: 99%
“…As an approximation, we represented the maximum enhanced fluorescence as the largest intensity of the bursts in the time trace, subtracting the background. 45 Those maximum bursts are around 55 counts/ ms, whereas the background is 16 counts/ms. To get the enhancement factor, we evaluated the fluorescence signal of one NDI-2TEG-3T molecule from a high-concentration solution (50 μM) by recording the fluorescence signal under the same experimental conditions but on an area without a nanorod.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, there are other alternative methods to obtain the enhancement factor from the same type of experimental data, leading to similar results. 41 …”
Section: Resultsmentioning
confidence: 99%
“…We think this reflects the variation in near-field distributions of individual gold nanorods and shows the promise of our method for their characterization. Despite these differences, individual nanorods, once calibrated with a standard or an appropriate optical technique, such as enhanced fluorescence, 36 may be used for the accurate sizing of analytes. Furthermore, we have demonstrated that our system is capable of recognizing single analyte particles with 5 nm diameter at lower concentration levels of ∼10 nM.…”
Section: Discussionmentioning
confidence: 99%